On the long-ignored scientific achievements of the Belgica expedition 1897–1899 - De Deckker, Patrick (Polar Research, 2018)
The Belgica expedition, which left Belgium in August 1897, was the first to spend 13 months continuously in Antarctic waters, before returning in late 1899. This was not only an exploratory venture, as new lands and oceans were charted, but more importantly it was an exceptional and successful scientific voyage. After the return of the expedition, a vast array of scientific data was processed and eventually 92 publications in some nine volumes funded by the Belgica Commission appeared over 40 years as a series called Résultats du voyage de la Belgica en 1897–99 sous le commandement de A. de Gerlache de Gomery – rapports scientifiques. Disappointingly, those significant results have been mostly ignored in the scientific literature and the paper here aims to inform scientists of the achievements of the Belgica expedition and where to obtain the information. Many of the climatological and oceanographic data obtained by the expeditioners ought to be examined in line with the changes that are occurring today in the Antarctic Peninsula region as a result of global warming. Some of the Belgica data form an important database to critically assess environmental changes over 120 years in the region of the Antarctic Peninsula.
Keywords: Antarktis; Belgica ekspedisjon; glasiologi; global oppvarming; klimaendringer; klimatologi; meteorologi; miljøendringer; oppdagelsesreiser; oseanografi; vitenskap